2015
DOI: 10.11124/jbisrir-2015-2444
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of midwives and nurses collaborating to provide birthing care: a systematic review

Abstract: Qualitative evidence about the experiences of midwives and nurses collaborating to provide birthing care was identified, appraised and synthesized. Two synthesized findings were created from the findings of the five included studies. Midwives and nurses had negative experiences of collaboration which may be influenced by: distrust, unclear roles, or a lack of professionalism or consideration. Midwives and nurses had positive experiences of teamwork which can be a source of hope for overcoming the challenges of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 32 publications
0
21
0
1
Order By: Relevance
“…Collaborative maternity care promotes respectful and active participation of each discipline involved ( Macdonald et al. , 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Collaborative maternity care promotes respectful and active participation of each discipline involved ( Macdonald et al. , 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Many midwives report challenges when there is little inter-professional knowledge and respect for their distinct role in achieving optimum health outcomes for mother, infant and family. Facilitators for collaboration include clarity of roles, mutual respect, shared values or vision and a willingness to collaborate ( Macdonald et al. , 2015 ; Waldman et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Las matronas y las enfermeras tuvieron experiencias positivas de trabajo en equipo que pueden ser una fuente de esperanza para superar los desafíos de compartir la atención; por lo tanto, es necesario desarrollar e implementar estrategias que aborden y minimicen las ocurrencias de estos tres elementos en un esfuerzo por reducir las experiencias de colaboración negativas para parteras y enfermeras. Las experiencias positivas de trabajo en equipo deben reconocerse y celebrarse, y los desafíos que presenta compartir la atención deben entenderse como parte del proceso colaborativo (Macdonald et al 2015).…”
Section: Análisisunclassified
“…A review of serious case reviews involving children found that most failings were due to poor interprofessional communication, interprofessional disagreement, interprofessional conflict, power differences in teams, documentation, not speaking and or sharing information, and poor or inadequate interagency communication 5. A systematic review examining midwives' and nurses’ collaborative experience found negative experiences might be influenced by distrust, unclear roles, or a lack of professionalism or consideration 6. Interprofessional working in both the clinical and academic settings requires competence, commitment, and the desire and will to cooperate.…”
mentioning
confidence: 99%